Attitudes pregnant women in Türkiye towards holistic complementary and alternative medicine and influencing factors: a web-based cross-sectional study - Burcu Küçükkaya; Hafsa Kübra Işık (BMC Complementary Medicine and Therapies, 2023)
Abstract Background Pregnant women turn to holistic complementary and alternative medicine to cope with problems associated with the changes they experience during pregnancy. This study aimed to determine the attitudes of pregnant women in Türkiye toward holistic complementary and alternative medicine and influencing factors. Methods This cross-sectional exploratory study was carried out between June and November 2022 with a web-based questionnaire distributed via social media and communication platforms. Two hundred and twenty-one pregnant women participated in the study. A "Participant Identification Form" and the "Attitudes towards Holistic Complementary and Alternative Medicine Questionnaire" were used to collect the data. Logistic regression analysis was used to determine correlations between variables and scale scores. Results It was determined that 84.2% of the participants had knowledge about traditional and complementary therapies, and 77.8% used traditional and complementary therapies. The participants reported that they preferred faith (77.4%), energy healing (76.9%), massage (75.6%), diet (74.2%), meditation/yoga (62.0%), and herbal (59.7%) traditional and complementary therapies the most, and most of them used these methods to reduce nausea, vomiting, edema, and fatigue during pregnancy. The mean Attitudes towards Holistic Complementary and Alternative Medicine Questionnaire score of the participants was 35.0 (5.04). It was seen that having high school or higher education (p < 0.05), having an income more than expenses (p < 0.001), having received advice from nurses when having a complaint (p < 0.001), having knowledge about traditional and complementary therapies (p < 0.001), and being a practitioner who received services of traditional and complementary therapies (p < 0.001) were positively associated with the utilization of traditional and complementary therapies. Conclusion In this study, it was determined that the attitudes of pregnant women towards holistic complementary and alternative medicine were high. Their personal characteristics, as well as their knowledge and practice of holistic complementary and alternative medicine affected their attitudes towards holistic complementary and alternative medicine. Obstetrics nurses/midwives should actively participate in training programs on traditional and complementary therapies focused on pregnant women.